Existence of Steady-State Equilibria in Matching Models with Search Frictions - Stephan Lauermann; Georg Nöldeke (University of Basel, Center of Business and Economics (WWZ), 2014)
We prove existence of steady-state equilibrium in a class of matching models with search frictions.
Keywords: C62; C78; D83; 330; Search; Matching; Bargaining; Steady-State Equilibrium